Effect of Repetitive Transcranial Magnetic Stimulation on a Target Moving in Front of a Static or Random Dynamic Visual Noise. (August 2020) - Battaglini, Luca
Observers report seeing as slower a target disk moving in front of a static visual noise (SVN) background than the same object moving in front of a random dynamic visual noise (rDVN) background when the speed is the same. To investigate in which brain region (lower vs. higher visual areas) the background and the target signals might be combined to elicit this misperception, the transcranial magnetic stimulation (TMS) was delivered over the early visual cortex (V1/V2), middle temporal area (MT) and Cz (control site) while participants performed a speed discrimination task with targets moving in front of an SVN or an rDVN. Results showed that the TMS over MT reduced the perceived speed of the target moving in front of an SVN, but not when the target was moving in front of an rDVN background. Moreover, the TMS do not seem to interfere with encoding processing but more likely affected decoding processing in conditions of high uncertainty (i.e., when targets have similar speed).